2014
DOI: 10.20885/iustum.vol21.iss1.art7
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Penanganan Tanah Terlantar di Kabupaten Tasikmalaya dan Kabupaten Sukabumi dalam Mewujudkan Ketahanan Pangan Provinsi Jawa Barat

Abstract: This research discusses the problems of: first, the implementation of the Government Regulation No 11 of 2010 on the Control and Utilization of Deserted Land in Tasikmalaya Regencykendala dalam memetakan tanah yang terindikasi terlantar karena pada faktanya identifikasi dan penelitian tidak dilakukan dengan melibatkan instansi yang kewenangannya terkait dengan penetapan tanah terlantar. Kedua, pendayagunaan tanah terlantar belum diarahkan untuk menambah dan mengoptimalkan penyediaan lahan pertanian sehingga pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several studies have examined the impact of climate change on livelihoods in Indonesia. For example, a study by [22], [25] examined the effects of climate change on livelihoods in districts in West Java Province, including the Sukabumi Regency. The study found that climate change could significantly affect livelihoods in the area, especially for farmers and other individuals who rely on agriculture as a source of income.…”
Section: Food Security and Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the impact of climate change on livelihoods in Indonesia. For example, a study by [22], [25] examined the effects of climate change on livelihoods in districts in West Java Province, including the Sukabumi Regency. The study found that climate change could significantly affect livelihoods in the area, especially for farmers and other individuals who rely on agriculture as a source of income.…”
Section: Food Security and Climate Changementioning
confidence: 99%
“…For example, drought can reduce the availability of water for irrigation, which can affect rice production. In addition, temperature changes can affect the growth and development of rice plants, causing low yields [22].…”
Section: Introductionmentioning
confidence: 99%
“…Prioritizing utilization efforts also means minimizing conflicts and disputes that have the potential to occur. 31 Internally, the inhibiting factor for controlling abandoned Land is that, in general, the Land Office experiences technical, administrative, and financial support problems in implementing these provisions. 32 Determination of the criteria for abandoned Land that has ownership rights to the Land that is owed in Article 7 points 2 a and b of Government Regulation No.…”
Section: Legal Implications Of Controlling Abandoned Land In Land Law...mentioning
confidence: 99%
“…Sebagai tanggapan, mendukung pertanian lokal telah muncul sebagai solusi yang tepat untuk mengatasi masalahmasalah yang saling terkait ini. Dengan memprioritaskan praktik pertanian berkelanjutan, mengurangi jarak tempuh pangan, meningkatkan ketahanan pangan, melestarikan lingkungan, dan mendorong pengembangan masyarakat, pertanian lokal memiliki potensi untuk mengubah sistem pangan kita dan menciptakan masa depan yang lebih berkelanjutan (Nurlinda et al, 2014;Riajaya & Munandar, 2020;Sugiman, 2019;Sunaryo & Nuraini, 2021).…”
Section: Dalam Hal Pengembangan Masyarakat Pendekatan Pengembanganunclassified